Intratumoral neutrophil extracellular traps are associated with unfavorable clinical outcomes and immunogenic context in pancreatic ductal adenocarcinoma - Chen, Xianlong; Ma, Heng; Mo, Shengwei; Yu, Shuangni; Lu, Zhaohui; Chen, Jie (Frontiers in Immunology, 2022)
Extracellular traps (ETs) and tumor-infiltrating immune cells play crucial roles in tumor progression. However, little is known about the clinical significance of tumor-infiltrating neutrophils and macrophages and the related ETs in pancreatic ductal adenocarcinoma (PDAC). This study investigates the associations between neutrophil or macrophage infiltration or ET formation and the clinicopathological features, molecular characteristics, immune checkpoint molecules, clinical outcomes, and response to adjuvant chemotherapy (ACT) in PDAC. We performed multiplex immunofluorescence staining to detect ET formation by neutrophils or macrophages using tissue microarrays obtained from 205 patients, and analyzed the immunohistochemistry data for PD-L1, PD-L2, B7-H3, and B7-H4. The ET expression rates in macrophages and neutrophils were 23.9% and 45.4%, respectively. Patients with a high density of neutrophils or positive expression of neutrophil ETs exhibited poorer progression-free survival (PFS) and disease-specific survival (DSS), whereas macrophage ETs were not related to PFS and DSS. Neutrophil infiltration and ET formation were identified as independent prognostic predictors of DSS using univariate and multivariate Cox analyses. Patients with PDAC with lower neutrophil infiltration or negative staining for neutrophil ETs are more likely to benefit from ACT. Patients with PDAC were more accurately stratified based on the infiltration of neutrophils and presence of neutrophil ETs, and patients with low neutrophil infiltration or negative staining for neutrophil ETs showed the best survival. Patients with positive neutrophil ETs demonstrated inferior DSS compared to those with negative neutrophil ETs in the PD-L1 tumor proportion score (TPS) < 1% and PD-L1 IC < 1% subgroups. However, the positive expression of neutrophil ETs was not related to DSS in the PD-L1 TPS ≥ 1% or PD-L1 IC ≥ 1% subgroup. Our findings emphasize the potential of neutrophil infiltration and ETs as prognostic markers that could guide the formulation of more effective personalized treatments for PDAC.